Inherent thermodynamic performance assessment of a variable refrigerant flow system under transient cooling load: A case study of an eco-villa - Muhammad Reshaeel; Mohamed I. Hassan Ali (Case Studies in Thermal Engineering)
Variable refrigerant flow systems are recognized for their energy efficiency, yet their performance under fluctuating cooling loads and interdependencies among intrinsic performance variables remains insufficiently explored. This study investigates the thermodynamic and environmental performance of a variable refrigerant flow system for an eco-villa in Masdar City, Abu Dhabi, under dynamic operating conditions. A mathematical model exhibiting a coefficient of determination of 0.89, a mean absolute error of 0.04, and a mean square error of 0.01, has been developed in MATLAB to evaluate system behavior. Analysis of the system's intrinsic performance variables reveals its ability to dynamically adjust compressor speed in response to fluctuating cooling loads, enhancing isentropic efficiency. This dynamic adaptability results in a reduction in power consumption by 11.1 % and an enhancement in the coefficient of performance by 12.5 % during minimum load conditions compared to constant-speed compressors. Energy and exergy evaluations indicate that cooling load profiles dominate system performance. Compressor power ranges from 6.06 kW at peak load conditions to 2.64 kW at minimum load conditions, with the corresponding increase in the coefficient of performance (3.73–4.40) and exergy efficiency (36.91 %–43.58 %), and a decrease in exergy destruction (2.95–1.05 kW). Statistical analysis using Pearson correlation highlights strong interdependencies among variables, including ambient temperature's positive correlation with compressor speed (0.89) and condensation temperature's negative correlation with isentropic efficiency (−0.22). Conversely, evaporation temperature shows a positive correlation with isentropic efficiency (0.29), enhancing system performance and reducing exergy destruction. Finally, the environmental evaluation analysis a 15.38 % reduction in annual energy consumption and a 1.51-ton reduction in carbon dioxide emissions per eco-villa annually, scaling to 1509.75 tons for 1000 villas, underscoring the system's potential for energy efficiency and environmental sustainability.